Methods in iPSC technology - Birbrair, Alexander (Advances in stem cell biology ;, 2021)
The series Advances in Stem Cell Biology is a timely and expansive collection of comprehensive information and new discoveries in the field of stem cell biology. iPSCs - Novel Concepts, Volume 15 addresses how important induced pluripotent stems cells are and how can they can help treat certain diseases. Somatic cells can be reprogrammed into induced pluripotent stem cells by the expression of specific transcription factors. These cells have been transforming biomedical research over the last 15 years. This volume will address the advances in research of how induced pluripotent stem cells are being used for treatment of different disorders, such as liver disease, type-1 diabetes, Parkinson's disease, macular degeneration of the retina and much more. The volume is written for researchers and scientists in stem cell therapy, cell biology, regenerative medicine and organ transplantation; and is contributed by world-renowned authors in the field.